(untitled) (Research, Society and Development, 2021)
The COVID-19 is a disease caused by the mutation of the SARS-COV2 virus, which brought to global health one of the most laborious challenges in history, the year 2020 is being marked as the greatest pandemic of the 21st century, since the new disease there are still unknown aspects, becoming a challenge for professionals working in the front line, especially Nursing. To characterize the actions of the Urgent Nurse in the fight against COVID-19 evidenced in the literature and to analyze the assistance of the Urgent Nurse in the Fight against COVID-19, according to scientific publications This is an integrative review study of the literature developed through the search publications in the Medline, BDENF, LILACS, IBECS, R. Multimídia, PAHO-IRIS, LIS e Coleciona SUS. The study showed new publications about nursing care to COVID-19, demonstrating that these actions are under construction, which reinforces the need for studies, mainly related to the particularities of the virus. In addition, it showed the importance of nursing management for the construction of care and the impacts on the nurse’s professional life. It is concluded that nursing care is essential to provide care to patients with suspected or confirmed COVID-19, requiring the expansion of studies, training and qualification to improve care.